Nanoscale fissure formation in AlxGa1–xN/GaN heterostructures and their influence on Ohmic contact formation. Issue 1 (25th October 2016) - Smith, M. D.; Thomson, D.; Zubialevich, V. Z.; Li, H.; Naresh‐Kumar, G.; Trager‐Cowan, C.; Parbrook, P. J.
Abstract : Nanoscale surface fissures on Al x Ga1– x N/GaN (15 nm/1 µm) heterostructures grown by metalorganic vapour phase epitaxy (MOVPE) were imaged using tapping‐mode atomic force microscopy (AFM) and electron channelling contrast imaging (ECCI). Fissure formation was linked to threading dislocations, and was only observed in samples cooled under H2 and NH3, developing with increasing barrier layer Al content. No strain relaxation was detected regardless of fissure formation up to barrier layer Al composition fractions of x  = 0.37. A reduction of measured channel carrier density was found in fissured samples at low temperature. This instability is attributed to shallow trap formation associated with fissure boundaries. For Ti/Al/Ni/Au Ohmic contact formation to high Al content barrier layers, fissures were found to offer conduction routes to the 2DEG that allow for low resistance contacts, with fissure‐free samples requiring additional optimisation of the metal stack and anneal conditions to achieve contact resistivity of order those measured in fissured samples. In addition, the effects of fissures were found to be detrimental to thermal stability of sheet and contact resistance, suggesting that fissure formation compromises the integrity of the 2DEG.